About rodents : a guide for children - Sill, Cathryn P., 1953-; Sill, John (Atlanta : Peachtree, 2008)
Simple text and colorful illustrations introduce various rodents, discussing their physical characteristics, their behaviors, their diet, their common habitats, and the animals who are their predators.
A Junior Library Guild selection
Includes bibliographical references.
Keywords: Rodents -- Juvenile literature; Rodents; Rodents